Language classroom anxiety: a comparative study of ESL learners / Voviana Zulkifli - Zulkifli, Voviana (ACRULeT, Faculty of Education & UiTM Press, 2007)
Malaysia decided use English as the medium of instruction at university level beginning 2002 and much debate has surfaced since then. English has also increased in importance in the People’s Republic of China (PRC) since the nation joined the World Trade Organization (WTO) and implemented an Open Door Policy. This study compares perceived second language anxiety and attempts to identify significant differences in the level of anxiety of male and female ESL university students at Stamford College, Petaling Jaya, Selangor, Malaysia and from the PRC Malaysia. It also attempts to identify the factors that could contribute to language classroom anxiety. Although the study did not control for factors that may influence language apprehension, the results suggest that nearly half of the total number of respondents are anxious about learning the English language. The English Language Classroom Anxiety Scale (ELCAS) with 32 items was constructed and used for the purpose of the study which was adapted from the Foreign Language Classroom Anxiety Scale (FLCAS) (Horwitz et al. 1986). Findings show that gender is of slight significance but nationality is an important variable in identifying the anxiety level with the various factors that may contribute to English language classroom anxiety